Community knowledge, attitudes and practices related to Taenia solium taeniosis and cysticercosis in Zambia - Zulu, Gideon; Mwape, Kabemba E.; Welte, Tamara M.; Simuunza, Martin C.; Hachangu, Alex; Mutale, Wilbroad; Chembensofu, Mwelwa; Sikasunge, Chummy S.; Phiri, Isaac K.; Winkler, Andrea S. (Plos Neglected Tropical Diseases, 2023)
Background Several studies on Taenia solium taeniosis / cysticercosis (TSTC) have been conducted in Zambia. However, none has assessed community knowledge, attitudes and practices related to TSTC and epilepsy. Methods A community-based cross-sectional study was conducted between November and Decem-ber 2022. The design consisted of a questionnaire-based survey conducted in each of the 25 purposely selected villages in Chiparamba Rural Health Centre (RHC) catchment area in Chipata district of the Eastern Province. Results A total of 588 participants comprising 259 (44%) males and 329 (56%) females with median age of 42 years (range 17 to 92 years) were interviewed. Awareness of the signs and symptoms of taeniosis and human cysticercosis (HCC), including transmission and prevention measures was very low. Whilst the majority had heard about epilepsy, they were not able to link HCC to epilepsy. Most participants were aware of cysticerci in pigs (PCC) including its predilection sites but were not aware of mode of transmission and prevention measures. The pork meat inspection by trained professionals was also not a common practice in the area. Risk perception of T. solium infections was thus very low. Overall knowledge, attitude and practice scores related to T. solium infections and to epilepsy were very low with median scores of 0.38 (IQR 0.25–0.54) for knowledge, 0.25 (0.25–0.50) for attitudes, and 0.31 (0.25–0.44) for practices. Males had better knowledge on TSTC (median = 0.42, p = 0.017, r = 0.098) and better practice scores (median = 0.38, p = < 0.001, r = 0.154) compared to females though the effect size was small. With regards to sanitation and hygiene washing with soap and water was reported by many but only few had a hand washing facility near their latrines. Conclusion The study shows overall poor knowledge, attitudes and practices related to TSTC among the community of Chiparamba RHC in Chipata district of the Eastern Province of Zambia. This poses a serious challenge for control and elimination of T. solium infections and thus efforts to improve knowledge, attitudes and practices should be made using a One Health approach for the control and elimination of TSTC. Educational programs about TSTC trans-mission, signs and symptoms, prevention, management and control need to be scaled up in the study area and Zambia as a whole.
CRIS-Team Scopus Importer:2023-09-15